Microeconometric analysis of firm level adjustment to globalisation - Pisu, Mauro (2005)
The globalisation process of national economies, through trade and foreign direct investment flows, has been one of the most important forces of economic changes in the latest decades. This thesis contributes to the growing literature on firm level adjustment to globalisation. This literature initiated a new paradigm in international trade based on heterogeneous firms. The recent availability of large firm-level data sets and new theoretical models allow to examine how heterogeneous firms react to internationalisation processes, and how their responses determine changes at more aggregate levels. In each chapter of this dissertation we deal with one different aspect of firm-level adjustment to globalisation processes using a data set of manufacturing firms based in the United Kingdom. The United Kingdom is a good example of a globalised economy given that it is second largest host of multinational enterprises and relatively open to international trade. Overall, our results support the view that heterogeneous firm-level adjustments are important to our understanding of the impact of internationalisation processes on national economies. We argue and find evidence (in chapter two) that import competition does not necessarily lead to higher elasticity of the demand for labour at firm and industry-level, as it has been claimed before. Furthermore, we show (in chapter three) that foreign affiliates contribute disproportionately to the export performance of United Kingdom manufacturing sectors. The export decisions of multinational enterprises seem to depend on motives different from those of domestic firms. Finally, we present evidence (in chapter four) of the relationship between firm-level productivity and participation to globalisation processes, through trade or foreign direct investment, comparing not means, but productivity distribution functions, which allows to account for the heterogeneity of productivity level across firms. In general, these findings underline the importance of building from micro economic evidence to gauge the likely impact of globalisation processes on national economies.